Do tourists dream of urban air mobility? psychology and the unified theory of acceptance and use of technology - Radic, Aleksandar; Quan, Wei; Ariza-Montes, Antonio; Koo, Bonhak; Kim, Jinkyung Jenny; Chua, Bee-Lia; Gil-Marín, Miseldra; Han, Heesup (Routledge, 2024)
Traffic congestion is a widespread problem that can affect tourists at psychological, cognitive, physical, and social levels. Some cities are solving traffic congestion better than others. The purpose of this study is to unearth the perception of U.S. and Chinese tourists toward the adoption of urban air mobility (UAM). The novelty of the current study dwells in introducing avoidance, hyper-arousal, impairment in functioning and somatization as antecedences of emotional exhaustion and depersonalization and combining emotional exhaustion and depersonalization with the modified Unified Theory of Acceptance and Use of Technology (UTAUT) 2 model. The prospective conceptual framework explained the influencing predominance produced by the dependent variables: intention to use UAM (88.3%), emotional exhaustion (60.9%) and depersonalization (72.0%) for Chinese tourists and intention to use UAM (76.6%), emotional exhaustion (68.4%) and depersonalization (61.3%) for U.S. tourists. We found that emotional exhaustion, depersonalization and modified UTAUT 2 constructs have a significant effect on the intention to use UAM for urban tourism.